Fabrication of magnesium-hydroxyapatite composites targeted for biodegadable implant application - Saifulrizan Mokhtar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
In the present study, as a lightweight metal with mechanical properties similar to natural bone, magnesium is gaining wide popularity as biodegradable materials targeted for temporary implant applications. the objective of the present work is to fabricate magnesium based metal matrix composites (MMC) for f=degradable impalant applications and hydroxypatite (HA) powder was selected as the secondary phase.